Time and Performer Training - Evans, Mark; Thomaidis, Konstantinos; Worth, Libby (Taylor & Francis, 2019)
Time and Performer Training addresses the importance and centrality of time and temporality to the practices, processes and conceptual thinking of performer training. Notions of time are embedded in almost every aspect of performer training, and so contributors to this book look at: age/aging and children in the training context, how training impacts over a lifetime, the duration of training and the impact of training regimes over time, concepts of timing and the 'right' time, how time is viewed from a range of international training perspectives, collectives, ensembles and fashions in training, their decay or endurance. Through focusing on time and the temporal in performer training, this book offers innovative ways of integrating research into studio practices. It also steps out beyond the more traditional places of training to open up time in relation to contested training practices that take place online, in festival spaces and in folk or amateur practices. Ideal for both instructors and students, each section of this well-illustrated book follows a thematic structure and includes full-length chapters alongside shorter provocations. Featuring contributions from an international range of authors who draw on their backgrounds as artists, scholars and teachers, Time and Performer Training is a major step in our understanding of how time affects the preparation for performance.